2008
DOI: 10.1164/rccm.200712-1822oc
|View full text |Cite
|
Sign up to set email alerts
|

Essential Role of Pre–B-Cell Colony Enhancing Factor in Ventilator-induced Lung Injury

Abstract: Rationale: We previously demonstrated pre-B-cell colony enhancing factor (PBEF) as a biomarker in sepsis and sepsis-induced acute lung injury (ALI) with genetic variants conferring ALI susceptibility. Objectives: To explore mechanistic participation of PBEF in ALI and ventilator-induced lung injury (VILI). Methods: Two models of VILI were utilized to explore the role of PBEF using either recombinant PBEF or PBEF 1/2 mice. Measurements and Main Results: Initial in vitro studies demonstrated recombinant human PB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
154
1
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(165 citation statements)
references
References 49 publications
8
154
1
2
Order By: Relevance
“…2A). Retrospective review of our prior expression profiling results in murine models of VILI indicated that D2 mRNA was induced in VILIchallenged WT mice (9.5-fold increase at 30 mL/kg tidal volume and 26.2-fold increase at 40 mL/kg tidal volume) (36,37).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…2A). Retrospective review of our prior expression profiling results in murine models of VILI indicated that D2 mRNA was induced in VILIchallenged WT mice (9.5-fold increase at 30 mL/kg tidal volume and 26.2-fold increase at 40 mL/kg tidal volume) (36,37).…”
Section: Resultsmentioning
confidence: 99%
“…Groups of mice (WT, n = 8 mice per group; D2KO, n = 6 mice per group; D1KO, n = 6 mice per group; hypothyroid WT mice, n = 6 mice per group) were allocated randomly to either the SB or VILI treatment as previously described (36,37). Mechanical ventilation experiments were performed in age-matched males after anesthesia with inhaled isofluorane followed by i.p.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…NAMPT expression also affected the expression of two other inflammatory cytokines (IL-16 and CCR3 genes) [22,23]. Hong et al [24] demonstrated recombinant human NAMPT as a direct rat neutrophil chemotactic factor in in vitro studies. They also demonstrated a marked increase in bronchoalveolar lavage leukocytes after the intratracheal injection of rhNAMPT into C57BL/6J mice.…”
Section: Physiological Functions Of the Nampt Genementioning
confidence: 99%